2011
DOI: 10.1029/2010wr009480
|View full text |Cite
|
Sign up to set email alerts
|

Operational real‐time modeling with ensemble Kalman filter of variably saturated subsurface flow including stream‐aquifer interaction and parameter updating

Abstract: Urban groundwater is frequently contaminated, and the exact location of the pollution spots is often unknown. Intelligent monitoring of the temporal variations in groundwater flow in such an area assists in selectively extracting groundwater of drinking water quality. Here an example from the city of Zurich (Switzerland) is shown. The monitoring strategy consists of using the ensemble Kalman filter (EnKF) for optimally combining online observations and online models for the real‐time characterization of ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 46 publications
1
54
0
2
Order By: Relevance
“…Hendricks Franssen and Kinzelbach [18] obtained best results with a combination of all three techniques. Hendricks Franssen et al [20] observed filter inbreeding when analyzing variably saturated flow through a randomly heterogeneous porous medium with NMC = 100 even after dampening log-conductivity fluctuations by a factor of 10. Several authors (e.g., [21][22][23][24]) have seen a reduction in filter inbreeding effects through covariance localization and covariance inflation.…”
Section: Introductionmentioning
confidence: 97%
“…Hendricks Franssen and Kinzelbach [18] obtained best results with a combination of all three techniques. Hendricks Franssen et al [20] observed filter inbreeding when analyzing variably saturated flow through a randomly heterogeneous porous medium with NMC = 100 even after dampening log-conductivity fluctuations by a factor of 10. Several authors (e.g., [21][22][23][24]) have seen a reduction in filter inbreeding effects through covariance localization and covariance inflation.…”
Section: Introductionmentioning
confidence: 97%
“…Applications of Kalman filter approaches in a geo-scientific context can be found in many documented studies. To name just a few: in reservoir engineering, smart well and history matching concepts are designed using Kalman filter approaches (Jansen et al 2009;Heidari et al 2011;Hu et al 2012); in hydrogeology and geosciences, different inverse problems are solved including the updating of permeability patters (Hendricks et al 2011) or the data assimilation applied to a estuarine system (Bertino et al 2002). The application of these techniques is not known in solid mineral resource extraction applications, particularly not for updating resource and reserve models based on sensor data.…”
Section: Fig 1 Correlation Between Sensor-based Measurements and Labmentioning
confidence: 99%
“…Each numerical element of the groundwater flow model is coupled to a one-dimensional (1-D) model for vertical flow in the vadose zone. For numerical and computational convenience capillary forces are neglected and only gravity-driven flow is considered, which is an option in the MIKE SHE code (Graham and Butts, 2005). Streamflow is simulated using the kinematic routing option.…”
Section: Modelmentioning
confidence: 99%
“…This study uses a transient, spatially distributed hydrological model based on the MIKE SHE code (Graham and Butts, 2005). This code considers all major components of the land phase of the hydrological cycle and the code allows the hydrological components to be dynamically coupled, meaning that feedback (i.e.…”
Section: Modelmentioning
confidence: 99%